Poor Sleep and Decision-Making Disturbance Are Associated With Suicidal Ideation in Pre-natal Depression - Bao, Ciqing; Xu, Ling; Tang, Weina; Sun, Shiyu; Zhang, Wenmiao; He, Jincai; Zhao, Ke; Xu, Dongwu; Ye, Xiaodan (Frontiers in Psychiatry, 2021)
Although many risk factors for suicidal ideation have been identified, few studies have focused on suicidal ideation and prenatal depression. The purpose was to investigate the relationship between decision-making (DM) dysfunction and sleep disturbance on suicidal ideation in prenatal depression. Participants included 100 women in the third trimester of pregnancy, including pregnant women with prenatal depression who had recent suicidal ideation (n = 30), prenatal depression without SI (n = 35) and healthy controls (n = 35). The Iowa Gambling Task (IGT) was used to evaluate the DM function and the Pittsburgh Sleep Quality Index (PSQI) was used to assess the sleep index. The Edinburgh Postnatal Depression Scale (EPDS) was used to assess suicidal ideation and the seriousness of depression. Overall, the two groups with prenatal depression showed worse sleep quality and decreased DM function compared with healthy controls. The prenatal depression with suicidal ideation group showed a significantly higher score in subjective sleep quality and a lower score in block 5 of IGT than the prenatal depression without suicidal ideation group. Further correlation analysis showed that suicidal ideation positively correlated with subjective sleep quality, sleep duration, and daytime function, and negatively correlated with IGT scores. Sleep disturbance and impaired DM function may be risk factors for suicidal ideation in prenatal depression.